To Be a Female Slave: American Slavery and Women - Mahnigová, Jana (Univerzita Pardubice, 2014)
This work focuses on the analysis of Uncle Tom´s Cabin by Harriet Beecher Stowe and slave narratives by Harriet Ann Jacobs and by Sojourner Truth. The main aim of the paper is to show how slavery disrupts slave mother-child relationships. It is explained who is depicted to be responsible for the intrusion into slave families, and how mothers act when the bond to their children is endangered. The paper also deals with literary techniques the authors use to emphasize the brutality of slavery as this would affect Americans´ position on slavery.
Otroctví v Americe a ženy
Keywords: otroctví v Americe; vztahy mezi otrokyněmi a jejich dětmi; Uncle Tom´s Cabin; Incidents in the Life of a Slave Girl; Narrative of Sojourner Truth; American slavery; slave mother-child relationships